Exhaustive endurance training for 6-9 weeks did not induce changes in intrinsic heart rate and cardiac autonomic modulation in female athletes - Uusitalo, A. L.; Uusitalo, A. J.; Rusko, H. K. (International Journal of Sports Medicine, 1998)
We investigated the effects of progressively increased training load and overtraining on resting and intrinsic heart rate (IHR) and cardiac autonomic modulation (CAM), and their relationships to performance variables. Nine athletes (ETG) increased training volume at 70-90% of maximal oxygen uptake (VO2max) by 130% (p<0.01) and training volume at <70% VO2max by 100% (p < 0.01) during 6-9 weeks. The corresponding increases in six female control athletes (CG) were 5 and 10%. Pharmacological blocking through atropine and propranolol and the Rosenblueth and Simeone model were used to calculate the sympathovagal balance index (Abal) and to measure IHR. The results were analysed using two-way analysis of variance. VO2max, IHR and Abal did not change. Resting heart rate had a tendency to decrease in the ETG and increase in the CG during the training period (interaction p < 0.01). Five ETG athletes demonstrated overtraining state (OA subgroup). Their VO2max (mean+/-SEM) decreased from 53.0+/-2.2 ml x kg(-1) x min(-1) to 50.2+/-2.3 ml x kg(-1) x min(-1) (p < 0.01), but no changes in resting HR, IHR and Abal were found. A significant correlation between the baseline values of VO2max and the parasympathetic activity index was found (r=-0.59, p < 0.05). In conclusion, progressively increased training load and overtraining did not induce significant changes in intrinsic heart rate or cardiac autonomic modulation in female endurance athletes. Resting heart rate rather decreased with heavy endurance training and overtraining. High maximal oxygen uptake was correlated with high cardiac parasympathetic modulation.